Knowledge, attitudes, and use of the Mediterranean diet in practice among dietitians in the United Arab Emirates: a cross-sectional study - Salma Abu-Qiyas; Hadia Radwan; Leila Cheikh Ismail; Mohamad Alameddine; Mariam Muayyad; Farah Naja (Scientific Reports)
Abstract Dietitians are uniquely positioned to promote the Mediterranean Diet (MedDiet), a diet recognized for its health benefits and sustainability. This study aimed to assess the knowledge and attitudes regarding the MedDiet among dietitians in the United Arab Emirates (UAE), and to examine the frequency and correlates of using this diet in clinical practice. Practicing dietitians (n = 220) completed a 44-item web-based questionnaire, verified for face, content and construct validity, as well as internal and parallel form reliability. Total scores were computed as sum of items for knowledge and attitudes. The mean knowledge score was 6.48 ± 1.85 out of 10, with gaps related to MedDiet’s benefits and nutrient composition. Despite positive attitudes, many dietitians did not agree that it is easy to encourage patients to decrease red meat (68%) and increase fruits/vegetables intake (70%). In clinical practice, 35% of dietitians rarely/never used the MedDiet. Dietitians were more likely to recommend the MedDiet if they had a Mediterranean country of origin (p = 0.037), higher knowledge (p = 0.022) and attitude (p = 0.013) scores, and acquired information about the MedDiet through university education (p = < 0.001) or conferences/seminars/workshops (p = 0.002). Using the findings of this study, evidence-based interventions can be developed to support the role of dietitians in promoting adherence to the MedDiet.